2011
DOI: 10.1080/10509674.2011.582932
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Assessment of Faith-Based Programs: Do Faith-Based Programs “Work” to Reduce Recidivism?

Abstract: Faith-based organizations administer many of the prison-based programs aimed at reducing recidivism. Many of these organizations also manage treatment programs for substance abusers, at-risk juveniles, and ex-offenders. Much of the research on religiosity and delinquency indicates that the two are inversely related. Therefore, it seems plausible that faith-based programs, which are rooted in religious organizations, may be effective tools for reducing deviant and criminal behavior. However, it is unclear wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 15 publications
2
33
0
3
Order By: Relevance
“…Longitudinal research corroborated these findings, suggesting that desistance from crime is related to formation of social ties (i.e., Laub and Sampson ). Recent research has examined the efficacy of faith‐based programs in reducing recidivism and found religion to be effective in rehabilitation (i.e., Dodson, Cabage, and Klenowski ; Jensen and Gibbons ; Johnson ; O'Connor and Perreyclear ; O'Connor, Ryan, and Parkikh )…”
Section: Literature Reviewmentioning
confidence: 99%
“…Longitudinal research corroborated these findings, suggesting that desistance from crime is related to formation of social ties (i.e., Laub and Sampson ). Recent research has examined the efficacy of faith‐based programs in reducing recidivism and found religion to be effective in rehabilitation (i.e., Dodson, Cabage, and Klenowski ; Jensen and Gibbons ; Johnson ; O'Connor and Perreyclear ; O'Connor, Ryan, and Parkikh )…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dodson, Cabage, and Klenowski (2011) state that historically, before the 20 th century, religious beliefs strongly influenced carceral policy.…”
Section: )mentioning
confidence: 99%
“…Reform efforts based on Judeo-Christian values were implemented to some degree with the objective being to offer prisoners time for spiritual introspection (Dodson et al, 2011).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations